L’evoluzione dell’infosfera come emergenza di un terzo connettoma - Mori, Luca (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
Information flows and communicative interactions on social media, theWeb and the expanding Internet of things are changing the possibilities, the actual methods and models of interaction between human beings, objects and life environments. As a result, an unprecedented landscape of structural and functional connections emerge that can be described, at least in part, in terms of connectivity graphs.